Fatty Acid Composition of Muscle, Adipose Tissue and Liver from Muskoxen (Ovibos moschatus) Living in West Greenland. - Susana P Alves; Katrine Raundrup; Ângelo Cabo; Rui J B Bessa; André M Almeida (PLoS ONE, 2015)
Information about lipid content and fatty acid (FA) composition of muskoxen (Ovibos moschatos) edible tissues is very limited in comparison to other meat sources. Thus, this work aims to present the first in-depth characterization of the FA profile of meat, subcutaneous adipose tissue and liver of muskoxen living in West Greenland. Furthermore, we aim to evaluate the effect of sex in the FA composition of these edible tissues. Samples from muscle (Longissimus dorsi), subcutaneous adipose tissue and liver were collected from female and male muskoxen, which were delivered at the butchery in Kangerlussuaq (West Greenland) during the winter hunting season. The lipid content of muscle, adipose tissue and liver averaged 284, 846 and 173 mg/g of dry tissue, respectively. This large lipid contents confirms that in late winter, when forage availability is scarce, muskoxen from West Greenland still have high fat reserves, demonstrating that they are well adapted to seasonal feed restriction. A detailed characterization of FA and dimethylacetal composition of muskoxen muscle, subcutaneous adipose tissue and liver showed that there are little differences on FA composition between sexes. Nevertheless, the 18:1cis-9 was the most abundant FA in muscle and adipose tissue, reaching 43% of total FA in muscle. The high content of 18:1cis-9 suggests that it can be selectively stored in muskoxen tissues. Regarding the nutritional composition of muskoxen edible tissues, they are not a good source of polyunsaturated FA; however, they may contribute to a higher fat intake. Information about the FA composition of muskoxen meat and liver is scarce, so this work can contribute to the characterization of the nutritional fat properties of muskoxen edible tissues and can be also useful to update food composition databases.